En Atlantique, dans le parfum du grogú : la valorisation de la canne à sucre aux îles du Cap-Vert - Michel Lesourd (Caravelle)
The Cabo Verde archipelago’s history cannot be dissociated from the sugar cane’s one. This plant, appreciated by the peasants because of its advantages in spite of poor hydric conditions, is found in all the systems of agricultural production. Along with other plants, it has contributed to perpetuate the archipelago’s territorial and socially unequal structure. The actual demand, due to diaspora as well as tourism, bears the revival of its culture which appears in el grogú, a home-made rhum, considered as an identity marker as well as a local product with standard qualifications.